The Phenomenon of Kinship Politics in the 2024 Election on Bangka Island - Aprillia, Donna Ardila; Ibrahim; Hidayat, Novendra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
The practice of kinship politics leads to the regeneration of power for the benefit of certain groups, namely children, husbands, wives, younger siblings with the aim of gaining or maintaining power. Many family members of political officials on Bangka Island will run in the 2024 election. The results showed that there was kinship politics in the 2024 election on Bangka Island in the families of H. Sukirman, Riza Herdavid, and Maulana Aklil. This form of kinship politics includes direct support from the family and the influence of kinship that rules the region. The development of kinship politics in Bangka Island is due to factors of political elites who want to maintain or perpetuate power, party attitudes that are still pragmatic, weak regeneration, political opportunities for kinship politics, people who vote are still pragmatic, and an election system that provides space for thepractice of kinship politics.